Information practices of administrators for controlling information in an online community of new mothers in rural America. (3rd August 2022) - Potnis, Devendra; Halladay, Macy
Abstract: Rarely does any empirical investigation show how administrators routinely control information in online communities and alleviate misinformation, hate speech, and information overload supported by profit‐driven algorithms. Thematic analysis of in‐depth phone interviews with members and administrators of a "Vaginal Birth After Cesarean" (VBAC) group with over 500 new mothers on Facebook shows that the administrators make 19 choices for recurring, authoritative but evolving 19 information‐related activities when (a) forming the VBAC group over Facebook for local new mothers, (b) actively recruiting women who had a VBAC or have related competencies, (c) removing doctors and solicitors from the group, (d) setting up and revising guidelines for interactions in the group, (e) maintaining the focus of the group, (f) initiating distinct threads of conversations on the group, (g) tagging experts during conversations in the group, and (h) correcting misinformation. Thirty‐eight information practices of the administrators indicate their nine gatekeeping roles, seven of these roles help administrators alleviate misinformation, hate speech, and information overload. Findings also show that the management of members and their interactions is a prerequisite to controlling information in online communities. Prescriptions to social networking companies and guidelines for administrators of online communities are discussed at the end.